An Analysis of Writers’ Errors in Producing Descriptive Texts; Intercultural Studies - Erickson, Ebidel (Universitas Pendidikan Mandalika, 2022)
In EFL context, errors analysis is done to illuminate the comprehension to improve learners’ writing processes and products. In grammatical construction, language grammars or structures must reflect the flexibility and conventionality of language usage and language users’ knowledge. This study aimed at identifying errors made by international learners at English studies programs in producing descriptive texts. This study was working in qualitative ways. 13 international learners who took master study of English studies are involved in this study. The sample was taken using purposive random sampling. The gender consisted of 7 females and 6 males. The level of English proficiencies is considered as the same level because the sample was bestowed Indonesian, Brazilian, Malaysian, and South Africa scholarship, in which the international English language testing system was achieved the passing grade. To gain the data, the researcher employed writing tests with asking the sample to describe their home town and families. The data are analyzed using qualitative works, i.e., data condensation, data display, and conclusion. Based on the data analysis, international learners still do some errors in producing descriptive texts. The errors covered omission, addition, selection or mis-formation, and mis-ordering. The errors are caused by misconception and misinterpretation of English. They try to transfer their language knowledge from their native language to their national language, then into target language (English). They have three transferring processes in mind. It is a strong possibility that makes them do some language errors in producing their writing products. Therefore, this study can be concluded that international learners who learn English in foreign countries still do such kinds of errors in producing their writing products.